Perbandingan Kinerja Pelayanan Sebelum Dan Sesudah Penerapan Simrs Di Rumah Sakit Tipe B - Irma, Eka; Rista, Indriana; Hartono, Budi; Daud, Alfani Ghutsa (Innovative: Journal Of Social Science Research, 2025)
The improvement of healthcare service quality demands hospitalsto adopt modern management systems, one of which is through theimplementation of the Hospital Management Information System (SIMRS). This study aims to analyze the comparison of serviceperformance before and after the implementation of SIMRS in a type B hospital, focusing on service time efficiency, the quality ofmedical record documentation, inter-unit coordination, and usersatisfaction. This research uses a descriptive qualitative approachwith a case study method conducted at a type B hospital in Pekanbaru City that has implemented SIMRS for more than oneyear. Data were collected through observation, in-depthinterviews, and documentation. The results show that theimplementation of SIMRS has had a positive impact on improvingservice efficiency, accelerating the registration and medicationretrieval processes, and enhancing the accuracy of medicalrecords and inter-unit coordination. However, the success ofSIMRS implementation is strongly influenced by infrastructurereadiness, staff training, and management support. SIMRS has a positive impact on enhancing service efficiency. This study recommends periodic evaluation of system performance andstrengthening of human resource capacity to optimize the benefitsof SIMRS in supporting fast, accurate, and high-qualityhealthcare services.